Imaging in Percutaneous Musculoskeletal Interventions - Gangi, Afshin.; Guth, Stp̌hane.; Guermazi, Ali. (Medical Radiology, Diagnostic Imaging,, 2009)
This is one of the first books to deal specifically with imaging in percutaneous musculoskeletal interventions. The use of different imaging modalities during these procedures is well described. In the first chapter, the basic procedures and different guidance techniques are presented and discussed. The ensuing chapters describe in exhaustive detail the abilities and uses of imaging in guiding procedures ranging from biopsy and joint injection to management of pain and tumors. These procedures are extensively documented in adults as well as in the pediatric population. The third part of the book describes the different indications for vascular interventions in musculoskeletal lesions. The final chapter focuses on ultrasound-guided interventions, as they are more common and tend to be fashionable. The book is well illustrated with carefully chosen and technically excellent images. Each of the 18 chapters is written by an expert of international repute, making this book the most current and complete treatment of the subject available. It should be of great interest to interventional radiologists and also musculoskeletal and general radiologists.